(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Background: Lateral Epicondylitis (LE) is a common overuse injury of Elbow that generates pain over the lateral aspect of elbow. LE is one of the most common causes of elbow and forearm pain encountered in clinical practice commonly associated with resistant wrist or finger extension and gripping activities. The management of LE is enlightened by various form physical modalities and therapeutic exercise like stretching and strengthening exercise. The purpose of this prospective study was to investigate the effects of stretching and strengthening exercises on pain and grip strength of LE. Materials and methods : Eighty patients were enrolled, non-randomized, and divided into 2 groups an experimental Group-A of 40 (44.5 ± 1.5 years) whose receive therapeutic exercise in the form of stretching and strengthening of common extensor forearm muscle and a control Group-B of 40 (41.4 ±2.5 years). Study duration was about one year. Both Group received UST over the lateral aspect of elbow with the 3MHz frequency and 0.5 watt/cm2 intensity for 5 min three sessions per week for six weeks. They were evaluated at every weeks of treatment for six weeks. Comparison between Group-A and Group-B was done with Wilcoxon Rank sum test and unpaired ttest. Results: By the end of the trial period, statistical data analysis in between the two groups showed a significant improvement in pain scores of VAS and the maximal isometric grip strength at sixth week. Conclusion: This study depicts that therapeutic exercise is more effective in reducing pain and improvement of grip strength. So, stretching and strengthening exercise should be considered as a main therapeutic armamentarium in the management of LE. JCMCTA 2019 ; 30 (1) : 36-42